Enhancing institutional integration and enjoyment among Saudi female physical education students: exploring the mediation of motivation and psychological needs satisfaction - Frikha, Mohamed; Chaâri, Nesrine; Mezghanni, Nourhen; Hassan, Ahmad K.; Alhumaid, Majed M.; Alibrahim, Mohammed S. (Frontiers in Education, 2024)
Institutional integration and enjoyment in physical education (PE) represent catalysts for greater students' social cohesion and academic performance. This cross-sectional study addressed the lack of data and examined the mediating effect of basic psychological needs satisfaction (PNS) and motivation on the association between physical activity enjoyment (PAE) and institutional integration (SII) in Saudi female PE students. Participants (N = 507) were invited to complete the PE autonomy relatedness competence scale, the PE motivation scale, the students' institutional integration scale, and the enjoyment questionnaire. The direct and indirect effects were explored using the SPSS Hayes process macro (Model 4). The results indicate that autonomy, relatedness and extrinsic motivation partially mediate the relationship between the PAE and SII in female Saudi PE students. Therefore, the PAE had a direct effect on SII of 16.2% and an indirect effect of 25.3% through the mediation of autonomy, relatedness, and extrinsic motivation. The psychological processes that promote the development of SII are PAE, autonomy, relatedness, and extrinsic motivation but not intrinsic motivation nor competence. The results are discussed within the self-determination theory and can be used by benefic for students, teachers, administrators or program makers to support institutional integration and enjoyment perception in Saudi female PE students.